Pengaruh Ekuitas Merek Dan Label Halal Terhadap Keputusan Pembelian Produk Wardah Di Kabupaten Muaro Jambi - Tri Nabila Putri Andari; Putri Apria Ningsih; Firman Syah Noor (Transformasi: Journal of Economics and Business Management, 2023)
At this time, the development of various kinds of cosmetic brands is increasing and very diverse from time to time and products circulating are increasing rapidly, causing market competition. Everyone has their own choice in making a purchase decision. Brand equity and halal labels are one of the factors influencing purchasing decisions. This study aims to determine and analyze the effect of brand equity and halal labels on purchasing decisions for wardah products in the people of Muaro Jambi Regency, especially consumers at the 6666 beauty cosmetic shop. The number of samples in this study were 88 people using a non-probability sampling technique, namely purposive sampling. Data collection through questionnaires, observations, interviews as well as documentation. The results of the study show that brand equity has a positive and significant effect on purchasing decisions for wardah products. The halal label shows that there is a negative and insignificant effect on the decision to purchase wardah products. Brand equity and halal labels together have a significant effect on purchasing decisions for wardah products. This illustrates that the value of Adjusted R2 Square is 0.165, that the contribution of the independent variables and the dependent variable is 16.5% and 83.5% is influenced by other factors that are not part of this study.